Musik in Baden-Württemberg. Jahrbuch 2001 (Band 8) & 2003 (Band 11) - Günther, Georg (Stuttgart Metzler, 2001)
2001 (Band 8): Comprehensive studies on the life and work of female composers in Heidelberg and Karlsruhe form the focus of this year's yearbook. Other studies deal with Stuttgart court and church music from the 16th to the 20th century, Sigmund Hemmel's psaltery compositions, Johann Jakob Froberger's harpsichord suites, Johann Sigismund Kusser's sonatas, Johann Rudolf Zumsteeg's church cantatas and the reception of Giuseppe Verdi's works. Studies on Johann Samuel Welter and Ignaz Holzbauer round off the biographical and work analysis section. The essay section is supplemented by reviews of current publications (books, sheet music, recordings), the state music bibliography, the directory ‘New and restored organs’ and reports from the music departments of the state libraries in Karlsruhe and Stuttgart.
The yearbook 2003 has two main focuses: on the one hand the church music tradition in the 18th and 19th centuries with articles on Meingosus Gaelle, Justin Heinrich Knecht and Samuel Gottlieb Auberlen, among others, and on the other hand the repertoire of the Stuttgart Court Opera in the 19th century with articles on Berlioz and Auber.
Keywords: Music history; Female; Baden-Württemberg (Germany)